Natural resource scarcity and long-run development: central mechanisms when conditions are seemingly unfavourable - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
Using a dynamic model with non-renewable natural resources and endogenous knowledge creation, the paper analyses economic development under conditions which are generally considered as most unfavourable. We assume poor substitution between primary input factors, positive population growth and a limited supply of materials in the static part of the framework, as well as natural resources being an essential input into R&D, and constant or decreasing returns to innovative activities in the dynamic part. It is shown that there is an inverse relationship between input substitution and growth-enhancing sectoral change and that labour supply supports economic dynamics through the knowledge-creation effect. A permanent increase in living standards is achievable under free market conditions, but adjustment costs and errors in long-term expectations might impede this development.
Keywords: Q20; Q30; O41; O33; 330; endogenous technological change; environment; natural resources; sustainability